2014
DOI: 10.1115/1.4027189
|View full text |Cite
|
Sign up to set email alerts
|

Diesel-Ignited Propane Dual Fuel Low Temperature Combustion in a Heavy-Duty Diesel Engine

Abstract: D ep a rtm e n t o f M e cha n ical E n g in e erin g, C enter fo r A d va nce d V e h ic u la r S ystem s, M is s is s ip p i State U nive rsity, M is s is s ip p i State, M S 3 9 7 6 2 e -m a il: krishn a n @ m e .m sstate .e du D iesel-Ignited Propane Dual Fuel Low Tem perature Combustion in a Heavy-Duty Diesel EngineThis paper presents an experimental analysis of diesel-ignited propane dual fuel low tem perature combustion (LTC) based on performance, emissions, and in-cylinder combustion data from a modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Among gaseous primary fuels for dual fuel LTC, methane (or natural gas) has been investigated quite extensively. On the other hand, while conventional diesel-ignited propane dual fuel combustion has been studied by several researchers [38][39][40][41][42][43], very few studies have focused on propane as the primary fuel for dual fuel LTC (e.g., [44,45]). The present effort is an attempt to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among gaseous primary fuels for dual fuel LTC, methane (or natural gas) has been investigated quite extensively. On the other hand, while conventional diesel-ignited propane dual fuel combustion has been studied by several researchers [38][39][40][41][42][43], very few studies have focused on propane as the primary fuel for dual fuel LTC (e.g., [44,45]). The present effort is an attempt to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…The present effort is an attempt to fill this gap. Building on previous research efforts on dual fuel LTC at Mississippi State University (MSU) [34][35][36][44][45], this paper presents experimental results for diesel-ignited propane dual fuel LTC on a single-cylinder research engine (SCRE). Considering the wellestablished infrastructure for propane production and distribution within the United States, it is attractive as the primary fuel for dual fuel LTC.…”
Section: Introductionmentioning
confidence: 99%
“…Polk et al, in a 6-cylinder diesel engine with dual fuel combustion of low-speed and low-power propane-diesel fuel; investigated their effects on performance, combustion and emission values. In their results, they concluded that as the amount of propane increases, NOX and soot emissions approach zero, and on the other hand, the amount of propane used can be up to 93% by reducing the EGR ratio and increasing the inlet pressure (Polk et al, 2014).…”
Section: Avrupa Bilim Ve Teknoloji Dergisi E-issn: 2148-2683 284mentioning
confidence: 99%
“…In dual fuel engines, typically a low reactivity fuel is fumigated into the intake manifold where a high reactivity fuel is directly injected into the combustion chamber. There have been multiple studies performed on different fuel combinations for dual fuel engine operation such as diesel-methane (DM), 1,2 diesel-propane (DP), 3,4 diesel-gasoline (DG), [5][6][7] diesel-natural gas 8,9 diesel-butane (DB), 10 diesel-ethanol, [11][12][13] and biodiesel-CNG (BDCNG). 14 The dual fuel combustion concept is not recent, with one of the earliest studies of an engine operating with the dual fuel strategy performed by Riffkin.…”
Section: Introductionmentioning
confidence: 99%